(untitled) (Journal of Nepal Geological Society, 2000)
In the hilly area of Langa, which is situated to the south of the city of Alba between the Belbo and Bormida Valleys, the heavy rainfall and subsequent floods of 3-6 November 1994 triggered numerous landslides. The slides caused serious damage to residential areas and various types of infrastructure. Engineering geological, geomorphological, geotechnical, hydrogeological, and geophysical methods were applied to investigate the instabilities. Among hundreds of failures, most of them were planar slides and debris-mud flows. However, the numerous landslides directly connected to the event represent only a part of the large and varied types of phenomenon in this area. In fact, most of the recent landslides can be considered as reactivated older ones that were more-or-less quiescent. They intersect at the depth the marly basement and are directly connected to the recent geological and tectonic evolution of the area. The paper describes the mass movements and their causative factors. It also focuses on the hazards and risks associated with the instabilities, and their mitigation measures.